Quantifying exchangeable base cations in permafrost: a reserve of nutrients about to thaw - E. Mauclet; M. Villani; A. Monhonval; C. Hirst; E. A. G. Schuur; S. Opfergelt (Earth System Science Data, 2023)
Permafrost ecosystems are limited in nutrients for vegetation development and constrain the biological activity to the active layer. Upon Arctic warming, permafrost thaw exposes large amounts of soil organic carbon (SOC) to decomposition and minerals to weathering but also releases organic and mineral soil material that may directly influence the soil exchange properties (cation exchange capacity, CEC, and base saturation, BS). The soil exchange properties are key for nutrient base cation supply (Ca2+, K+, Mg2+, and Na+) for vegetation growth and development. In this study, we investigate the distributions of soil exchange properties within Arctic tundra permafrost soils at Eight Mile Lake (Interior Alaska, USA) because they will dictate the potential reservoir of newly thawed nutrients and thereby influence soil biological activity and vegetation nutrient sources. Our results highlight much lower CEC density in surface horizons (∼9400 cmolc m−3) than in the mineral horizons of the active layer (∼16 000 cmolc m−3) or in permafrost soil horizons (∼12 000 cmolc m−3). Together, with the overall increase in CEC density with depth and the overall increase in BS (percentage of CEC occupied by exchangeable base cations Ca2+, K+, Mg2+, and Na+) with depth (from ∼19 % in organic surface horizons to 62 % in permafrost soil horizons), the total exchangeable base cation density (Ca2+, K+, Mg2+, and Na+ in g m−3) is up to 5 times higher in the permafrost than in the active layer. More specifically, the exchangeable base cation density in the 20 cm upper part of permafrost about to thaw is ∼850 g m−3 for Caexch, 45 g m−3 for Kexch, 200 g m−3 for Mgexch, and 150 g m−3 for Naexch. This estimate is needed for future ecosystem prediction models to provide constraints on the size of the reservoir in exchangeable nutrients (Ca, K, Mg, and Na) about to thaw. All data described in this paper are stored in Dataverse, the online repository of Université catholique de Louvain, and are accessible through the following DOI: https://doi.org/10.14428/DVN/FQVMEP (Mauclet et al., 2022b).